2019
DOI: 10.3892/mmr.2019.10311
|View full text |Cite
|
Sign up to set email alerts
|

Serum and tissue proteomic signatures of patients with hepatocellular carcinoma using 2‑D gel electrophoresis

Abstract: Hepatocellular carcinoma (HCC) accounts for ~85% of primary liver cancer cases and is a leading cause of mortality worldwide. Effective early diagnosis is difficult for HCC; however, effective biomarkers may be beneficial for diagnosis. In the current study, serum samples, and HCC and adjacent tissue samples were obtained from patients with HCC for the detection of biomarkers using 2-D gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization-time of flight (TOF)/TOF mass spectrometry. The cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Apolipoprotein E (APOE) is a major apoprotein of the chylomicron and is involved in the lipoprotein-mediated lipid transport between organs via the plasma and the interstitial fluids. It has been reported that the expression of APOE positively correlates with the HCC tumor grade ( 39 ). In our dataset, APOE was found to be up-regulated in HCC tumor tissues and down-regulated in the CCA tumor tissues (compared with benign tissues), suggesting important differences in lipid metabolism between HCC and CCA.…”
Section: Resultsmentioning
confidence: 99%
“…Apolipoprotein E (APOE) is a major apoprotein of the chylomicron and is involved in the lipoprotein-mediated lipid transport between organs via the plasma and the interstitial fluids. It has been reported that the expression of APOE positively correlates with the HCC tumor grade ( 39 ). In our dataset, APOE was found to be up-regulated in HCC tumor tissues and down-regulated in the CCA tumor tissues (compared with benign tissues), suggesting important differences in lipid metabolism between HCC and CCA.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the introduction of these four antibodies for immunoaffinity separation was expected to enrich the EVs specific to lung cancer in the circulation system, despite the heterogeneous size distribution. From the EV extract, prepared in this study, 55 DEPs were selected by enhanced spot density, accounting for a larger DEP pool compared to that of previous studies, such as in cases of rheumatoid arthritis and liver cancer detection (28 and 24 DEPs, respectively) [ 26 , 27 ]. In addition, all DEPs were categorized as EV-associated proteins by the Exocarta database ( , accessed on 8 February 2020).…”
Section: Discussionmentioning
confidence: 99%
“…OSBPL10 may become a prognostic marker for gastric cancer [ 9 ] and B-cell lymphoma [ 10 ]. OSBPL11 is a potential marker for hepatocellular carcinoma [ 11 ]. An overall analysis of the functions of OSBPL families for prognoses in patients with PDAC still needs to be explored.…”
Section: Introductionmentioning
confidence: 99%